The cardiovascular toxicity of polystyrene microplastics in rats: based on untargeted metabolomics analysis - Song, Zikai; Wu, Haidi; Fang, Xiaoqi; Feng, Xuemin; Zhou, Liting (Frontiers in Pharmacology, 2024)
Background: Polystyrene microplastics (PS-MPs) exhibit multi-target, multi-dimensional, chronic, and low toxicity to the cardiovascular system. They enter the bloodstream through the gastrointestinal tract and respiratory system, altering blood parameters and conditions, inducing thrombotic diseases, and damaging myocardial tissue through the promotion of oxidative stress and inflammatory responses in myocardial cells. However, many of the links and mechanisms remain unclear. Methods: In this study, 48 wistar rats were randomly divided into four groups and exposed to different concentrations of PS-MPs: control group (0 mg/kg/d), low dose group (0.5mg/kg/d), middle dose group (5mg/kg/d) and high dose group (50mg/kg/d), with 12 rats in each group. After 90 consecutive days of intragastric administration of PS-MPs, biochemical markers in myocardium, aorta and blood were detected, and HE staining was performed to observe the toxic effects of PS-MPs on cardiovascular system. Furthermore, non-targeted metabolomics methods were used to analyze the effect of PS-MPs exposure on the metabolism of cardiovascular system in rats, and to explore its potential molecular mechanism. The results revealed no pathological changes in the heart and aorta following PS-MPs exposure. However, the myocardial enzyme levels in the high dose PS-MPs group of rats showed a significant increase. Moreover, exposure to polystyrene microplastics caused a disorder in lipid metabolism in rats, and led to an increase in indicators of inflammation and oxidative stress in myocardial and aortic tissues, but resulted in a decrease in the level of IL-6. Untargeted metabolomics results showed that metabolites with antioxidant and anti-inflammatory effects, including equol and 4-hydroxybenzoic acid, were significantly up-regulated. Conclusions: These results suggest that long-term exposure to high concentrations of PS-MPs may lead to abnormal lipid metabolism and cardiovascular system damage. The mechanism may be related to oxidative stress and inflammatory response. Exogenous antioxidants and changes in own metabolites may have a protective effect on the injury. Therefore, understanding the toxicological mechanism of PS-MPs not only helps to elucidate its pathogenesis, but also provides new ideas for the treatment of chronic diseases.